2018
DOI: 10.3390/su10082939
|View full text |Cite
|
Sign up to set email alerts
|

What are the Key Indicators of Mega Sustainable Construction Projects? —A Stakeholder-Network Perspective

Abstract: Mega sustainable construction projects (MSCPs) require complex system engineering. There are various indicators available to evaluate sustainable construction, and it is difficult to determine which the key indicators are among them. Existing studies do not adequately consider the stakeholders associated with the indicators of sustainable construction, leading to key decision-makers' lack of targeted management strategies to improve the sustainability level of MSCPs. Using literature analysis and expert interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…Stakeholders’ benefits should be guaranteed as well as parties involved should take part in the decision-making processes that will affect their health and happiness (Aapaoja and Haapasalo, 2014; Newcombe, 2003). The vital point in achieving the project success is by enabling an equilibrium within the benefits of different stakeholders (Karlsen, 2002; Rose and Ponnappa, 2012; Wu et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholders’ benefits should be guaranteed as well as parties involved should take part in the decision-making processes that will affect their health and happiness (Aapaoja and Haapasalo, 2014; Newcombe, 2003). The vital point in achieving the project success is by enabling an equilibrium within the benefits of different stakeholders (Karlsen, 2002; Rose and Ponnappa, 2012; Wu et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the current framework proposed only the ideal policy functions without taking into account the divergent opinions and perspectives from various stakeholders involved in sustainability transitions, which downgrades the effectiveness of the framework as ultimately, the success of a transition is dependent on the close collaboration and support from various industry players (Gan et al, 2018;Wu et al, 2018). Hence, it is advised that the future development of the framework could link the policy functions of innovation policy mix with the major types of perspectives on sustainability transitions existed in stakeholders, so that the policy functions could be more targeted on stakeholders with specific perspectives.…”
Section: Theoretical Contributions To Innovation Policy MIX For Energmentioning
confidence: 99%
“…Lu et al (2015) explored the evolution of the organizational network of a megaproject in China and then proposed corresponding governance strategies. Wu et al (2018) identified the key evaluation indicators of mega sustainable construction projects from a stakeholder-network perspective using social network analysis (SNA). In retrospect, this study finds that researchers mainly focus on the impact of different organizational network structures, such as organizational density and centrality, when examining project performance (Ling and Li, 2012; Zheng et al , 2016).…”
Section: Introductionmentioning
confidence: 99%